Tracheal Mucoepidermoid Carcinoma Mimicking Deteriorated Bronchial Asthma during Pregnancy - Takeshi Murakami; Yasuyuki Fujita; Kazuhiro Takamura; Shuichi Taniguchi; Chikara Fukuyama; Kousuke Marutsuka; Tomihiro Shimamoto (Case Reports in Obstetrics and Gynecology)
Primary bronchial tumors are extremely rare. However, symptoms, such as coughing and wheezing, are not specific to this disease, and primary bronchial tumors are often misdiagnosed as bronchial asthma. This report describes the case of a pregnant patient with a bronchial tumor that mimicked deteriorating bronchial asthma. A 37-year-old female patient suffered from repeated episodes of pneumonia since 26 weeks of gestation. Despite treatment, she suffered from another episode of pneumonia at 28 weeks of gestation. This was considered as deteriorating asthma. Bronchoscopy performed at 34 weeks of gestation showed a tumor in the left main lung bronchus, obstructing nearly 100% of the trachea. After cesarean delivery at 34 weeks, she underwent endoscopic bronchial tumor resection. Because of recurrent bronchial obstruction and the possibility of malignant disease, subsequent left main lung bronchial resection and bronchoplasty were performed. The pathological diagnosis was low-grade mucoepidermoid carcinoma. In conclusion, if pneumonia develops repeatedly during pregnancy, the possibility of bronchial tumor should be considered.